Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines

Organotin-oxometalate coordination polymer catalyzed oxyfunctionalization of monoterpenes - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Keywords: Heck reaction; kinetics; Palladacycle

Rate enhancement in palladium catalyzed Heck reactions by Lewis acid promoters - Sud, Abhishek; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Significant enhancement in the rate of Heck reactions has been achieved when catalytic amounts of Lewis acid (like FeCl(3)) promoters in the presence of trace amounts of water (> 2000 ppm) are used along with Pd complex catalysts. Experiments with different aryl halides, bases as well as olefins have been carried out to demonstrate the role of Lewis acid promoters. The increase in the reaction rates is due to the weakening of Ar-X bond by the Lewis acid in the manner similar to Friedel-Crafts reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Heck reaction; Lewis acid; Palladium; Promoters

Sulfonamide- and hydrazine-based palladium catalysts: stable and efficient catalysts for C-C coupling reactions in aqueous medium - Kumar, N. S. C. Ramesh; Raj, I. Victor Paul; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2007)
Syntheses of a novel family of sulfonamide-based palladium complexes and phenylhydrazine-based palladacycles are described. These catalysts are thermally stable, and not sensitive to air and moisture and some are completely soluble in water. These catalysts have shown excellent activity (good yields and high turnover numbers) and product selectivity in several arylation reactions including Suzuki, Heck, and Sonogashira reactions carried out totally under aqueous conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: arylation reaction; Heck reaction; palladium catalyst; Sonogashira reaction; Suzuki coupling reaction

PdCl2(bipy) complex - an efficient catalyst for Heck reaction in glycol-organic biphasic medium - Jagtap, Sangeeta Vijay; Deshpande, Raj Madhukar (Catalysis Today, 2008)
The Palladium complex PdCl2(bipy) (1) was found to be efficient in catalyzing the Heck reaction of aryl halides in a biphasic system comprising ethylene glycol along with an organic solvent. A proper tailoring of the organic phase ensured that the leaching of the catalyst to the organic phase was negligible. The catalyst was active for the Heck reaction of a number of olefins, aryl halides, in presence of organic and inorganic bases. The PdCl2(bipy) catalyst was stable and could be recycled for five times without any loss in activity and selectivity. A major advantage of this work is that unlike hitherto reported biphasic systems; it does not employ a water-soluble ligand to achieve biphasic catalysis. (c) 2007 Elsevier B.V. All rights reserved.
4th Asia-Pacific Congress on Catalysis, Nanyang Technol Univ, Singapore, SINGAPORE, DEC 06-08, 2006
Keywords: Biphasic catalysis; C-C coupling; Heck reaction; PdCl2(bipy) complex

Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

Synthesis of the reported protoberberine gusanlung D - Wakchaure, Prasad B.; Easwar, Srinivasan; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from homopiperonylamine or phenethylamine with homophthalic anhydride or 3,4-methylenedioxyhomophthalic acid, respectively, facile syntheses of the reported structures of (+/-)-gusanlung D and (+/-)-isogusanlung d were accomplished via regioselective reductive dehydration of the corresponding homophthalimides followed by an intramolecular acid-catalyzed or radical cyclization pathway. Starting from the corresponding suitably ortho-halogenated homophthalimides, the syntheses of dehydrogusanlung and dehydroisogusanhing D were completed via regioselective reductive dehydration followed by an intramolecular Heck coupling reaction as the key steps. The analytical and spectral data obtained for all four synthetic compounds differed from the reported data for natural gusanling D, and therefore the structural assignment of the natural product needs to be revised.
Keywords: gusanlung D; Heck reaction; homophthalic anhydride; homopiperonyl amine; reductive dehydration

Kinetics of the Heck reaction in biphasic organic-ethylene glycol medium - Jagtap, Sangeeta Vijay; Deshpande, Raj Madhukar (Reaction Kinetics Mechanisms and Catalysis, 2012)
PdCl2(bipy) was found to be an efficient and stable catalyst in biphasic medium (organic-glycol) for the Heck reaction. The kinetics of the Heck coupling of styrene with iodobenzene using the same catalyst was studied in a biphasic medium in a temperature range of 393-413 K. The rate was found to have a first order dependence tending to a fractional order, on the iodobenzene as well as catalyst concentration. The rate was found to have a complex dependence on the styrene concentration and passes through a maximum, showing typical substrate inhibition kinetics. The rate had a first order dependence on the base (morpholine) concentration. The trends observed for the influence of the different parameters on the activity of the catalyst are in agreement with the established mechanism for Heck reaction. An empirical rate model has been proposed to fit the observed rate data. The activation energy was found to be 72.91 kJ/mol. This is the first time that kinetic modeling of Heck reaction in a biphasic medium (organic-glycol) has been attempted.
Keywords: Biphasic catalysis; Heck reaction; kinetics; PdCl2(bipy) complex

Cinnamic acid derivatives via heck reaction in an aqueous-biphasic catalytic system with easy catalyst-product separation - Jagtap, Sangeeta Vijay; Deshpande, R. M. (Asian Journal of Chemistry, 2013)
A true biphasic [aqueous-organic] system for the coupling of water soluble sodium acrylate with different aryl halides for the synthesis of cinnamic acid derivatives has been developed, employing palladium catalysts that is soluble in organic phase. Amongst them, palladacycle was found to be stable in presence of water and could be recycled for four times with no loss in the activity. Such a system facilitates easy recycle of catalyst and also the removal of the salts from the catalyst phase, ensuring high activity with respect to cumulative turn over number (TON) and turn over frequency (TOF). The reaction was facilitated by organic as well as inorganic bases. The efficiency of the catalyst, role of organic/inorganic bases on the activity is reported.
Keywords: Biphasic catalysis; Heck reaction; Palladacycle; Separation

Palladium chloride catalyzed photochemical heck reaction - Waghmode, Suresh B.; Arbuj, Sudhir S.; Wani, Bina N.; Gopinath, Chinnakonda S. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2013)
PdCl2 catalyzed carbon-carbon bond formation (Heck reaction) between substituted aryl halides and olefins was carried out without a ligand, under irradiation with UV-visible light. The results demonstrated that UV-visible light accelerated the rate of the reaction, leading to an excellent yield of corresponding products. The recovered palladium nanoparticles could be thermally recycled several times. PdCl2 gave excellent conversion up to the fifth addition of substrate.
Keywords: C-C coupling; Heck reaction; iodobenzene; photochemical reaction

True water soluble palladium-catalyzed Heck reactions in aqueous-organic biphasic media - Jagtap, Sangeeta Vijay; Deshpande, Raj Madhukar (Tetrahedron Letters, 2013)
A stable water soluble palladium catalyst has been demonstrated for the Heck reaction in a biphasic medium (water-non-polar organic solvent). Biphasic Heck reactions reported till now generally employ a non-polar solvent along with an aqueous polar water miscible organic solvent as the second phase. The efficiency of the Pd complex of TOTPS [Trisodium salt of tri-(ortho-tolyl) phosphine tri sulfonate] for the vinylation of different aryl iodides and olefins is demonstrated. The advantages of a co-solvent for this biphasic system have also been shown. The catalyst has been recycled efficiently retaining the activity with negligible loss of catalyst and without leaching of the Pd. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aqueous biphasic catalysis; C-C coupling; Heck reaction; Water-soluble catalyst

Access to a stereoisomer library of solomonamide macrocycles - Jachak, Gorakhnath R.; Athawale, Paresh R.; Choudhury, Rahul; Kashinath, K.; Reddy, D. Srinivasa (Chemistry-An Asian Journal, 2019)
In an attempt towards understanding stereo-structure activity relationships (SSARs), we have prepared eight possible stereoisomers of solomonamide macrocycles, in particular, by changing the stereochemical pattern of non-peptide fragment AHMOA. Here, we have demonstrated different ways to construct three contiguous chiral centers present in solomonamide B macrocycle using substrate/reagent-controlled methods. These methods involve Brown crotylation, NHK reaction and Evans aldol addition as key steps to synthesize key non-peptide fragment. Further, these non-peptide fragments were converted to their corresponding macrocycles via ligand-free intramolecular Heck reaction.
Keywords: Crotylation; Heck reaction; Inflammation; Macrocycles; Stereochemistry

Palladium impregnated amine Co-condensed hexagonal mesoporous silica: a novel catalyst in tailoring suzuki and heck coupling reactions in base free condition - Das, Prangya Paramita; Prabhakaran, Vinod C.; Nanda, Samik; Sen, Debasis; Chowdhury, Biswajit (ChemistrySelect, 2019)
Palladium impregnated amine co-condensed hexagonal mesoporous silicas (HMS-X) were synthesized (sol-gel process) using different amines (Ethylene diamine and pyridine) of various concentrations (0.25 equiv. and 2 equiv.). The effect of amine concentration on the local structure of hexagonal mesoporous silica was studied. The catalyst shows excellent catalytic activity and high TOF towards both Suzuki and Heck coupling reactions without using any base in reaction medium with the solvent DMF:water in (1:1) ratio. The catalyst was reused and it was recyclable up to three cycle without any appreciable loss of activity and the kinetics of the reaction varying different parameters also have been studied thoroughly.
Keywords: Amine functionalized silica; Base free; Heck reaction; Palladium supported catalysts; Suzuki reaction

Pd-catalyzed annulation of beta-iodovinyl sulfones with 2-halophenols: a general route for the synthesis of 3-sulfonyl benzofuran derivatives - Reddy, Raju Jannapu; Kumar, Jangam Jagadesh; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2020)
The palladium-catalyzed annulation between beta-iodovinyl sulfones and 2-halophenols or 1-bromo-2-naphthol or 2-bromo-3-pyridinol is presented. The annulation process involving oxa-Michael addition-elimination and intramolecular Heck reaction leading to form 2,3-disubstituted benzofurans (aryl benzofuryl sulfones) in good to high yields. The regioselective tandem construction of C-O and C-C bonds has been achieved with a variety of substitution patterns. Moreover, the tandem process is reliable at gram-scale reactions and a plausible mechanism is also proposed.
Keywords: Benzofurans; beta-Iodovinyl sulfones; Heck reaction; Naphthofurans; oxa-Michael addition